Geriatric Rehabilitation in Patients with Frailty: Interim Results of the POSTSCRIPTUM. An Open Prospective Study - Olga N. Tkacheva; Nadezhda K. Runikhina; Irina P. Malaya; Albert R Yusupov; Natalia V. Sharashkina; Valentina S. Ostapenko; Yulia V. Kotovskaya; Elen A. Mkhitaryan; Maria S. Arefieva; Evgenii Е. Popov; Elnura E. Esenbekova (Вестник восстановительной медицины)
INTRODUCTION. Introduction of additional stage of rehabilitation in elderly patients with varying degrees of frailty into practice helps to restore functional independence in patients, reduce the frequency of rehospitalizations and mortality in this population. Additional studies are needed in the Russian Federation for a wider integration of geriatric care models into clinical practice.